Benzothiadiazoloperylenes and Benzoxadiazoloperylenes: Amorphous Functional Materials - Langhals, Heinz; Knochel, Paul; Walter, Andreas; Zimdars, Silvia (Synthesis, 2012)
2,1,3-Benzothiadiazole or 2,1,3-benzoxadiazole were magnesiated (TMP2Mg·2LiCl) and efficiently attached to perylene and benzoperylene building blocks providing amorphous light-absorbing materials where FRET energy transfer proceeds between the 2,1,3-benzothiadiazole or 2,1,3-benzoxadiazole and the perylene units. Some of these new materials were obtained as amorphous solids of interest for material science.
Keywords: arenes; heterocycles; imides; cross-coupling fused-ring systems; zinc